Draft Genome Sequence of Rhodococcus Erythropolis b7g a Biosurfactant Producing Actinobacterium - Levican-Jaque, G; Retamal-Morales, G (Elsevier B.V., 2018)
Biosurfactants are amphipathic molecules with relevance in biotechnology due to their structural diversity, low toxicity and biodegradability. The genus Rhodococcus has extensively been studied because of its capacity to produce trehalose-containing surfactants as well as trehalose lipids as potential pathogenic factor. Here we present the draft genome sequence of Rhodococcus erythropolis B7g isolated with toluene from fuel-contaminated soil. The genome comprises 7,175,690 bp in 121 contigs, a G + C content of 62,4% and 7,153 coding DNA sequences (CDSs), and it contains genes for trehalose biosynthesis and surfactant production. Additionally, genes for the production of trehalose-tetraester biosurfactant were identified, whose function was experimentally verified making the strain B7g a potential candidate for use in bioremediation applications or in biosurfactant exploration. © 2018 Elsevier B.V.